2009
DOI: 10.1074/jbc.m109.014837
|View full text |Cite
|
Sign up to set email alerts
|

Redox Mechanisms Involved in the Selective Activation of Nrf2-mediated Resistance Versus p53-dependent Apoptosis in Adenocarcinoma Cells

Abstract: We have investigated the role of reactive oxygen species and thiol-oxidizing agents in the induction of cell death and have shown that adenocarcinoma gastric (AGS) cells respond differently to the oxidative challenge according to the signaling pathways activated. In particular, apoptosis in AGS cells is induced via the mitochondrial pathway upon treatment with thiol-oxidizing agents, such as diamide. Apoptosis is associated with persistent oxidative damage, as evidenced by the increase in carbonylated proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…In this case, the imbalance may be caused by the upregulated expression of proteins that compete for the binding sites of Nrf2/Keap1, including sequestosome-1 and prorhymosin-α (20)(21)(22), which results in the slower degradation of Keap1 and the overexpression of Nrf2. It has been suggested that HNE modifies Keap1, allowing Nrf2 to enter the nucleus to take effect (23,24). Future cellular studies are required to elucidate the effects of abnormal regulation and expression of the Nrf2/Keap1 pathway on the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the imbalance may be caused by the upregulated expression of proteins that compete for the binding sites of Nrf2/Keap1, including sequestosome-1 and prorhymosin-α (20)(21)(22), which results in the slower degradation of Keap1 and the overexpression of Nrf2. It has been suggested that HNE modifies Keap1, allowing Nrf2 to enter the nucleus to take effect (23,24). Future cellular studies are required to elucidate the effects of abnormal regulation and expression of the Nrf2/Keap1 pathway on the development of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Trx1 redox state was analyzed as previously described [14]. Briefly, cells were treated with cold TCA at final concentration of 10% for 30 min at 4 8C.…”
Section: Redox Western Blotmentioning
confidence: 99%
“…In this context, we have previously demonstrated that oxidative stress of different nature (ROS versus disulfide stress) can evocate opposite responses (cell death or survival), in the gastric adenocarcinoma cell line AGS, by means of the redox activation of specific signaling pathways [14]. In particular, we identified in the redox-dependent dissociation of Keap1/Nrf2 complex the event responsible for the resistance to ROS-mediated insults, and in the redox-activation of trx1/p38 MAPK /p53 signaling axis the pathway governing the induction of the apoptosis upon treatment with disulfide stressors (e.g., diamide).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrf2 activation may occur via direct or indirect phosphorylation of Nrf2 itself or regulator proteins by MAPKs (Li and Kong 2009). Activation of MAPKs cascades in response to oxidative stress is well documented; however, the specific molecular mechanisms of Nrf2 activation remain unclear (Piccirillo et al 2009). One potential mechanism is the phosphorylation of Cul3, a Nrf2 binding protein by MAPKs (Rachakonda et al 2008).…”
Section: Discussionmentioning
confidence: 99%